2011
DOI: 10.1007/s12275-011-1037-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory Activity of Dendritic cells pulsed with carbonic anhydrase IX and Acinetobacter baumannii outer membrane protein A

Abstract: Dendritic cell (DC)-based immunotherapy is a potent therapeutic modality for treating renal cell carcinoma (RCC), but development of antigens specific for tumor-targeting and anti-tumor immunity is of great interest for clinical trials. The present study investigated the ability of DCs pulsed with a combination of carbonic anhydrase IX (CA9) as an RCC-specific biomarker and Acinetobacter baumannii outer membrane protein A (AbOmpA) as an immunoadjuvant to induce anti-tumor immunity against murine renal cell car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Follow-up experiments using AbOmpA found that DCs pulsed with AbOmpA alone or in combination with autologous tumour cell lysates suppressed tumour growth in mice with a murine B16 melanoma [27]. More recently, we examined the immunostimulatory activity of DCs pulsed with a combination of CA9 and AbOmpA in vitro in order to determine the potential of AbOmpA in DC-based immunotherapy against RCC [37]. Use of a combination of CA9 and AbOmpA proteins resulted in more efficient induction of DC maturation and T cell response than CA9 alone, suggesting a potential of AbOmpA for enhancement of anti-tumour immune response against RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up experiments using AbOmpA found that DCs pulsed with AbOmpA alone or in combination with autologous tumour cell lysates suppressed tumour growth in mice with a murine B16 melanoma [27]. More recently, we examined the immunostimulatory activity of DCs pulsed with a combination of CA9 and AbOmpA in vitro in order to determine the potential of AbOmpA in DC-based immunotherapy against RCC [37]. Use of a combination of CA9 and AbOmpA proteins resulted in more efficient induction of DC maturation and T cell response than CA9 alone, suggesting a potential of AbOmpA for enhancement of anti-tumour immune response against RCC.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of OmpA to activate DCs was further supported by the observation that OmpA might function as an adjuvant in DC-based cancer immunotherapy (Kim et al, 2011(Kim et al, , 2012, in that OmpA-pulsed DCs significantly enhanced the number of IL-2 producing CD8 + T cells and IFN-γ producing CD4 + T cells, inhibited the tumor growth, and improved the survival of tumor-bearing mice (Lee et al, 2008;Kim et al, 2012). Although most studies showed that the immune responses induced by A. baumannii-activated DCs were primarily Th1 biased (Debarry et al, 2007(Debarry et al, , 2010, recent studies showed that OMVs from an A. baumannii clinical strain activated BMDCs to promote Th2 responses (Cai et al, 2019).…”
Section: Other Innate Immune Cellsmentioning
confidence: 91%
“…The main one was the use of dendritic cells (DCs, specific tumor antigen presentation) via an introduction of a granulocyte-macrophage colony stimulating factor (GMCSF)-CAIX fusion protein (produced by viral bioengineering), in order to activate DCs and thus trigger a CD8+ mediated, CAIX targeted, antitumoral response. Kim et al [ 50 ] presented the results of a pre-clinical study in 2011 aiming to activate DCs by a combination of CAIX and Acinetobacter baumannii outer membrane protein A (AbOmpA) in a murine model [ 51 ]. A significant immunostimulatory of DCs was observed via secretion of IL-2 and interferon (IFN)γ in T-cells.…”
Section: Evidence Synthesismentioning
confidence: 99%